Hungarian Monitoring, 2 March 1989 . [Magyar rádiófigyelő], 1989. március 2 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Tower case impact in US - Gun battles in Caracas - Marshall Akhromeev disputes Sakharov's statements on Afghanistan - Polish roundtable talks reach thorny stage - West Berlin representatives protest against neo-Fascists taking their seats Domestic Affairs: - Miklós Németh's Moscow work visit - Károly Grósz describes country's economic situation to Szolnok County representatives and asks them not to support the inclusion of Gabčíkovo-Nagymaros on the agenda - European Parliament delegation's visit - Péter Medgyessy vice premier has talks in Prague - Independent organizations hold protest this afternoon in Budapest for the release of V. Havel and intellectuals imprisoned after Prague demonstrations - Gyula Horn's talks in Bonn - Summary on the founding of the Social Democratic Party - Austria does not want to provide Hungary with a loan to support staging the World Exposition - Rezső Nyers holds Party activists' meeting at Inota - Miskolc city council decides to indefinitely postpone construction of controversial "Gypsy ghetto" Economy: - Fate of Mecsek coalmines discussed at ministerial tripartite committee meeting in Baranya Külpolitika: - A Tower ügy hullámai az Egyesült Államokban - Tűzharcok Caracasban - Ahromejev marsall cáfolta Szaharov Afganisztánnal kapcsolatos kijelentéseit - Kényes szakaszba jutottak a lengyel kerekasztal tárgyalások - A nyugat-berlini képviselők tiltakoztak, hogy újfasiszták foglalnak helyet a testületben Belpolitika: - Németh Miklós moszkvai munkalátogatása - Grósz K. Szolnok-megyei képviselők előtt az ország gazdasági helyzetét ecsetelte, majd arra kérte őket, ne támogassák a Bős-Nagymaros napirendre tűzését - Az Európa Parlament küldöttségének látogatása - Medgyessy P. miniszterelnök helyettes Prágában tárgyal - A független szervezetek kezdeményezésére ma délután tüntetés volt Budapesten V. HAVEL és a prágai megmozdulások miatt bebörtönzött értelmiségiek kiszabadításáért - Horn Gyula bonni tárgyalásai - Beszámoló a Szociáldemokrata Párt megalakulásáról - Ausztria nem kíván kölcsönt nyújtani Magyarországnak a világ - Kiállítás megrendezéséhez - Nyers Rezső Inotán tartott aktívaértekezletet - A miskolci városi tanács úgy döntött, hogy a vitatott "cigány gettó" építését bizonytalan időre elhalasztja Gazdaság: - A mecseki szénbányák sorsáról ún. miniszteri hármas bizottság tanácskozott Baranyában